Comparison of septic and nonseptic pulmonary embolism in children. Issue 10 (11th August 2021) - Gatt, Dvir; Ben‐Shimol, Shalom; Hazan, Guy; Golan Tripto, Inbal; Goldbart, Aviv; Aviram, Micha
Abstract: Background: Septic pulmonary embolism (SPE) in children is a rare disease. Data are scarce regarding the clinical and laboratory manifestation of SPE compared with nonseptic pulmonary embolism (ns‐PE). Furthermore, specific guidelines for the management of SPE in children are lacking. Aim: We compared the clinical course and outcome of children with SPE and ns‐PE. Methods: A retrospective, cohort study of hospitalized children, 2005–2020, with documented pulmonary embolism imaging. Results: Sixteen children (eight SPE, eight ns‐PE) were identified. Episodes of SPE occurred secondary to endocarditis, musculoskeletal and soft tissue infections, with Staphylococcus aureus ( n  = 4) and streptococcus spp. ( n  = 2) as the most common pathogens. Radiographically, SPE presented as a microvascular disease with parenchymatic nodules/cavitations, whereas ns‐PE presented as larger vessel disease with filling defects. Risk factors (including thrombophilia) were noted in 0% and 87.5% of SPE and ns‐PE patients, respectively ( p  < .01). Pulmonary embolism diagnosis was delayed in SPE compared with ns‐PE (median: 8.5 days vs. 1 day). The SPE group had higher rates of fever (100% vs. 12.5%, p  < .01), C‐reactive protein (CRP levels; 18.49 vs. 4.37 mg/dl, p  = .02), and fibrinogen levels (880 vs. 467 mg/dl, p  < .001). Antithrombotic treatment for >4 months was administrated to 14.3% and 87.5% of SPE and ns‐PE patients, respectively ( p  < .01). One ns‐PE patient had a second thromboembolic event compared to none in the SPE group. Conclusions: SPE in children is a unique subgroup of PE with different clinical and laboratory findings that requires a different diagnostic approach and probably shorter duration of antithrombotic treatment.